Effectiveness of Food Security Policy Implementation as An Efforts for Rehabilitation of Stunting Treatment in Rokan Hilir Regency - Yuliani, Febri; Sulistyani, Andri; Yusrizal, Firdaus; Islamiati, Indri (Indonesian Association for Public Administration (IAPA), 2024)
According to SDGs 2030, food security must have 3 principles, namely; Availability, Affordability; and Benefits, hereinafter referred to as food security aspects. Rokan Hilir is an area with a high level of stunting. Referring to the problem formulation, the objectives of this research are: 1) to analyze and describe the effectiveness of the implementation of the Food Security Policy; 2) to analyze and describe the factors that constrain the effectiveness of implementing the Food Security Policy in Rehabilitation Efforts to Handle Stunting in Rokan Hilir. The approach taken is a qualitative approach with descriptive analysis methods. The data required in this research consists of primary data and secondary data. The units of analysis in this research are people or parties who are considered to have knowledge about the implementation of food security policy innovations in dealing with stunting and also from the policy implementing apparatus, some of whom have certain positions, including staff, the community and also from NGOs which are parties involved in implementing food security policy innovations to combat stunting in Rokan Hilir. The research results show that stunting in children will have an impact on metabolic disorders, low immunity, and suboptimal physical body size. The better the coordination and communication between the parties involved in an implementation process, the less likely it is that errors will occur.